2012
DOI: 10.1093/cid/cis565
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trend of Necrotizing Fasciitis in Taiwan: Focus on Monomicrobial Klebsiella pneumoniae Necrotizing Fasciitis

Abstract: K. pneumoniae has become a common pathogen of monomicrobial NF in Taiwan. Physicians treating patients with monomicrobial KP-NF should be aware of the risk of concomitant distant abscesses, particularly in cases caused by genotype K1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
93
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 33 publications
5
93
4
Order By: Relevance
“…It can also affect ambulatory persons and cause community-acquired invasive diseases, including pyogenic liver abscess, endophthalmitis, meningitis, empyema, lung abscess, and necrotizing fasciitis (4)(5)(6)(7)(8)(9). The worldwide emergence of multidrug-resistant strains and hypervirulent strains of K. pneumoniae has become an increasing clinical challenge and public health concern (10,11).…”
mentioning
confidence: 99%
“…It can also affect ambulatory persons and cause community-acquired invasive diseases, including pyogenic liver abscess, endophthalmitis, meningitis, empyema, lung abscess, and necrotizing fasciitis (4)(5)(6)(7)(8)(9). The worldwide emergence of multidrug-resistant strains and hypervirulent strains of K. pneumoniae has become an increasing clinical challenge and public health concern (10,11).…”
mentioning
confidence: 99%
“…[14] Necrotizing fasciitis caused by K. pneumoniae is extremely rare in the western hemisphere, but necrotizing fasciitis caused by K. pneumoniae has been increasingly reported in the past decade, with fatality rates approaching 50%. [10,[17][18][19][20][21] In the current study, the mortality rates for diabetic patients in the V. vulnificus and K. pneumoniae groups were 10.5% and 27.2%, respectively, after early surgical debridement and adequate antibiotic treatment. We considered that capsule polysaccharides and lipopolysaccharides of K. pneumoniae can cause more immunologic defect and severe infections in the hyperglycemic status than that Metastatic infections with K. pneumoniae necrotizing fasciitis, which may be a consequence of transient bacteremia, have been reported.…”
Section: Discussionmentioning
confidence: 92%
“…Capsule polysaccharides and lipopolysaccharides, such as K1 and K2, are the most virulent serotypes and important virulence factors of K. pneumoniae. [17,18,20,22] Our previous studies showed that patients with hepatic dysfunction had significant associations with V. vulnificus infections; however, V. vulnificus can also produce severe sepsis in diabetic patients with or without other chronic illnesses. [14] Necrotizing fasciitis caused by K. pneumoniae is extremely rare in the western hemisphere, but necrotizing fasciitis caused by K. pneumoniae has been increasingly reported in the past decade, with fatality rates approaching 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 80% of these patients were diabetic. 9 A few fatal cases of Klebsiella NF have been reported from North America. 10 Interestingly, the cases of Klebsiella were more common among Asian population and those of Asian descent, hence raising the possibility of genetic susceptibility in these infections.…”
Section: Discussionmentioning
confidence: 99%